Stock price cycles and business cycles - Klaus Adam; Sebastian Merkel (European Central Bank (ECB), 2019)
We present a simple model that quantitatively replicates the behavior of stock prices and business cycles in the United States. The business cycle model is standard, except that it features extrapolative belief formation in the stock market, in line with the available survey evidence. Extrapolation amplifies the price effects of technology shocks and - in response to a series of positive technology surprises - gives rise to a large and persistent boom and bust cycle in stock prices. Boombust dynamics are more likely when the risk-free interest rate is low because low rates strengthen belief-based amplification. Stock price cycles transmit into the real economy by generating inefficient price signals for the desirability of new investment. The model thus features a "financial accelerator", despite the absence of financial frictions. The financial accelerator causes the economy to experience persistent periods of over- and under-accumulation of capital.
Keywords: E32; E44; G12; 330; business cycles; stock market volatility; booms and busts; financial accelerator